Stroke and risk factors for falls in elderly individuals - Alice Gabrielle de Sousa Costa; Ana Railka de Souza Oliveira-Kumakura; Thelma Leite de Araujo; Natália Barreto de Castro; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes (Rev Rene)
Objective: to verify and compare the intrinsic and extrinsic risk factors for falls among older community-dwelling people with and without a stroke history. Methods: a case group and three control groups were established and each group had 15 elderly individuals. Results: the statistical associations were: use of antihypertensive medication among the groups with falls, despite the occurrence of a stroke; use of angiotensin-converting enzyme inhibitor for elderly with a stroke who had an event of fall or not; foot alterations between the case group and people without falls or stroke. Gait difficulty and impaired physical mobility were statistically associated between the case group and people without the occurrence of stroke or falls. Conclusion: the stroke is associated with falls and the intrinsic factors presented greater statistical correlations, supporting the hypothesis that many factors influence the occurrence of falls.